Higher education and research: roots of mediocrity - Shah, A.M. (2005)
The fact that standards of higher education and research in universities in India have declined during the last few decades is widely recognised, but the fear that there are no signs of improvement is growing. Solutions have been sought mainly at higher levels of funding, particularly for hardware, and in minor administrative changes. Hardly any attempt is made to address the problems arising out of the long established basic structure of the university system and to deal with the changing ground realities. An attempt is made in this paper to draw attention to these and suggest a few thoughts on structural reform. - Reproduced.
Keywords: Educational research; Education; Higher education